Biallelic mutations in LARS2 can cause Perrault syndrome type 2 with neurologic symptoms. Issue 2 (3rd December 2017) - Kosaki, Rika; Horikawa, Reiko; Fujii, Eriko; Kosaki, Kenjiro
Abstract : Perrault syndrome represents a genetically heterogeneous disorder characterized by sensorineural hearing loss in males and females and ovarian dysfunction in females. Causative genes include HARS2, HSD17B4, CLPP, C10orf2, and LARS2 . Some patients with Perrault syndrome exhibit neurologic features including learning disability, cerebellar ataxia, and peripheral neuropathy and are classified as type 2 and are clinically separate from those without neurological symptoms other than a hearing loss (type 1). To date, all reported patients with LARS2 mutations (15 patients in 8 families) have been classified as type 1. Here, we report female siblings with biallelic mutations in LARS2, p.Glu294Lys, and p.Thr519Met, who were classified as type 2. The proposita developed progressive sensorineural hearing loss at 18 months and pervasive developmental disorder at 8 years, with repetitive behavior, insistence on sameness, attention deficit, tic, irritability, and an ataxic gait. At age 15 years, she was diagnosed as having primary amenorrhea with elevated FSH and LH and a decreased estradiol; ultrasound and magnetic resonance imaging examinations revealed a small uterus and no detectable ovaries. The proposita's younger sister presented with neonatal sensorineural hearing loss and a mild delay in motor and speech development. She was diagnosed as having primary amenorrhea with endocrinologic and radiographic findings that were comparable to those of her sister. She had difficulty with reading comprehension, and had trouble with open‐ended test questions at 12 years of age. We concluded that Perrault syndrome patients with LARS2 mutations are at risk for neurologic problems, despite previous notions otherwise.